A new species of Indonemoura (Plecoptera: Nemouridae) from Guangdong Province of southern China - Mo, Raorao; Wang, Guoquan; Yang, Ding; Li, Weihai (Zootaxa, 2019)
A new species of Nemouridae, Indonemoura bifida sp. nov., is described from Guangdong Province of southern China. This new taxon is compared with related congeners.